PENGARUH PERTIMBANGAN PASAR KERJA, GAJI DAN PERSONALITAS TERHADAP MINAT DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN PEMERINTAH - Widiartha, I Komang; Utama, I Made Karya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Career selection planning is important to achieve individual success. The choice of a career can be influenced by various factors such as labor market considerations, salary, and personality. The accounting field has a career scope such as government accountants, namely accountants who work for government agencies whose main task is to conduct audits of financial accountability. The number of accountants registered with professional associations of accountants in Indonesia was around 25,000 people in 2017. Furthermore, in 2020 there will be around 28,000 accountants (http://iaiglobal.or.id/). Although the number of accountants continues to grow every year, the need for accountants in the government sector is still high. The purpose of this study is to provide empirical evidence regarding the effect of labor market considerations, salary and personality on interest in choosing a government accountant career. The population in this study amounted to 235 students, with sampling using the method of determining purposive sampling and obtained a sample of 72 respondents. The data analysis technique in this study used multiple linear regression analysis. This research suggests that, job market considerations have a positive effect on students' career interests, salary has a positive effect on students' career interests, personality has a positive effect on students' career interests .